The hiding season : a novel - Glass, Ava, 1974- (Bantam Books, an imprint of Random House, 2026)
"After a painful divorce, Maya Landry is in desperate need of a fresh start, which she finds deep in the Rocky Mountains of Montana. Maya's relieved when she's hired as a summer keeper of billionaire-owned ski lodges left empty after snow season ends, and her new life of peace and isolation is going exactly as hoped ... until she stumbles across a dead body on the living room floor of one of the lodges. The killers don't want anyone left who knows what they've done. Forced to go on the run, Maya must rely on a mysterious stranger who offers to help her. But, surrounded by danger, can she trust him? Can she trust anyone?"--Flap page 1 of dust jacket.